Penyuluhan Knee Osteoarthritis kepada Pasien Prolanis di Puskesmas Kendalkerep Malang - Siti Chairun Ni’mah; Anita Faradilla Rahim (Jurnal Ventilator, 2023)
Osteoarthritis is a degenerative joint disorder that often occurs with age. This joint disorder can cause various kinds of problems that can interfere with daily activities, such as walking, going up and down stairs, sitting to standing position, prayer activities, standing too long, and so on. Community service activities are carried out by conducting counseling activities related to knee osteoarthritis. The purpose of the outreach activities carried out in the Prolanis community consisting of the elderly or elderly is to increase knowledge and understanding of the role of physiotherapy, especially regarding the management of physiotherapy related to the treatment of osteoarthritis through exercises that can be done independently at home. Physiotherapy management in osteoarthritis can be done using hamstring stretch exercises and quadriceps setting exercises.